2022
DOI: 10.1093/plphys/kiac445
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of the tomato fruit transcriptome under prolonged water stress

Abstract: Water availability influences all aspects of plant growth and development; however, most studies of plant responses to drought have focused on vegetative organs, notably roots and leaves. Far less is known about the molecular bases of drought acclimation responses in fruits, which are complex organs with distinct tissue types. To obtain a more comprehensive picture of the molecular mechanisms governing fruit development under drought, we profiled the transcriptomes of a spectrum of fruit tissues from tomato (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 130 publications
0
3
0
Order By: Relevance
“…Since many molecular factors may operate regardless of organ specificity, leaf and root organs should not be considered separately from the whole plant to understand the complex molecular network of drought response and its regulatory mechanisms. Finally, very few studies described GCNs involved in water stress response in tomato (Nicolas et al, 2022;Wei et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Since many molecular factors may operate regardless of organ specificity, leaf and root organs should not be considered separately from the whole plant to understand the complex molecular network of drought response and its regulatory mechanisms. Finally, very few studies described GCNs involved in water stress response in tomato (Nicolas et al, 2022;Wei et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This may underscore the significance of fruit photosynthetic activity during ripening. A recent study reported that fruit photosynthetic gene expression is upregulated in both green and ripened fruit under water stress when source capacity is constrained [ 71 ], indicating a dynamic tradeoff between source and sink photosynthesis to support organ development.…”
Section: Discussionmentioning
confidence: 99%
“…SGR1 is reported to be activated by fruit development and cold temperature 71 , suggesting our postharvest treatments may not have direct effect on chlorophyll degradation. A recent study reported that fruit photosynthetic gene expression is upregulated in both green and ripened fruit under water stress when source capacity is constrained 72 . This indicates a dynamic tradeoff between source and sink photosynthesis to support organ development.…”
Section: Discussionmentioning
confidence: 99%